Assessment on a regional scale of the geodiversity of the Southern Urban Agglomeration and its municipalities, Rio Grande do Sul coast, Brazil (Terr@ Plural, 2022)
The understanding of the relationships between abiotic components and these with the natural system, especially in coastal areas and densely occupied areas, such as urban agglomerations, has been important to support policies of conservation, preservation, and sustainable regional development.  In this sense, the aim of this study was to carry out an assessment on a regional scale of the geodiversity of the Urban Agglomeration of the South (AUSul), the coast of Rio Grande do Sul, and its constituent municipalities, through a geodiversity index and the occurrence and distribution of its elements in the region. To construct the index, the abiotic elements considered most relevant for the region's characteristics and the availability of data approximately compatible with the 1:250,000 scale was qualitatively defined. Subsequently, they were treated with methods of map algebra, resulting in the maps of the sub-indices related to geology, topography and geomorphology, hydrography and soils per municipality, and the geodiversity index of each municipality and the region. The results indicate the municipalities located on the Sul-Rio-Grandense Plateau and at the interface with the Coastal Plain with the highest indexes, being influenced by the greatest diversity of geological units, relief types, altimetric variations, and hydrographic features. Despite the significant occurrence of large wetland areas in the Coastal Plain municipalities, their indices were the lowest. The study proved to be useful for the understanding of the geodiversity of the AUSul, pointing out areas for studies at larger scales and macro-zoning, in addition to the need for complementation with methods that incorporate subjective characteristics of geodiversity.
Keywords: AUSul; Geodiversity index; Coastal Plain; Sul-Rio-Grandense Plateau; Geoconservation